Tourists' Perspectives on Condition of Heritage Buildings and Resiliency of the Heritage Tourism Industry in Melaka - Syed Mohamad, Syed Burhanuddin Hilmi; Abdul Rahman, Mohammad Ashraf; Suratkon, Azeanita; Shahrin, Farah (International Journal of Sustainable Construction Engineering and Technology, 2023)
Heritage buildings have been seen as an asset that needs to be maintained not only for the sake of history and culture but also as a legacy for future generations. In Melaka, heritage buildings have become a source of pride for the people of Malacca and also the main source of income for the state government through heritage tourism activities. It is important to ensure that these heritage buildings continue to recover and be free from damage so that the tourists who come have a good experience. This study is focused on the issues which were concerning the condition of heritage buildings in Malacca from the perspective of tourists. Heritage buildings around the tourist spot in Malacca were selected as locations for this study. The study adopted a questionnaire survey, that involved 211 local tourists as the respondents of the survey. The respondents were requested to gauge the conditions issue and the resiliency of heritage buildings using 5-points Likert scale. The collected data were analysed descriptively. The results found that the overall average condition issue mean value is high (M = 4.05) and can be interpreted as satisfactory. This indicates that the level of satisfaction with the condition received is high. Although most respondents expressed a good experience with the condition of the heritage buildings that they had visited, there is still room for improvements. The findings also show that all the agreement statements related to the resiliency of the heritage tourism industry in Melaka have an average score of 79%. As a result of the survey, it is important that the parties involved in heritage management follow the conservation standards, promote, and practice good integrity, especially in ensuring the originality and authenticity of materials used as well as good work procedures to ensure the future resiliency of the heritage tourism industry in Malacca.